Vibration Characteristics-based Isogeometric Analysis of Sandwich Plates with an Auxetic Honeycomb Core and Laminated Three-phase Skin Layers Resting on Kerr Foundation - Pham Binh Le; Chung Pham; Truong Thi Huong Huyen; Nguyen Manh Dung; Trung Thanh Tran (Journal of Applied and Computational Mechanics, 2025)
The main goal of this paper is to introduce an isogeometric analysis (IGA) procedure based on Reddy’s higher-order shear deformation theory (HSDT) for vibration analysis of sandwich plates resting on Kerr foundation (KF). The sandwich plates include the ultra-light feature of the auxetic honeycomb core layer and are reinforced by two laminated three-phase skin layers. The governing equation is derived from Hamilton's principle. The Newmark-beta method is applied to solve the vibration characteristics of the sandwich plates using the code in Matlab software. The reliability and accuracy of the proposed formula are verified through comparative examples. Additionally, the effects of geometrical dimensions, material properties, boundary conditions (BCs), and foundation stiffness on the vibration of sandwich plates are studied in detail. Our findings indicate that the initial geometry of the auxetic honeycomb core has a significant impact on the vibration characteristics of sandwich plates.